British Propaganda and News Media in the Cold War - Jenks, John (International Communications : INCO, 2022)
GBS_insertPreviewButtonPopup('ISBN:9780748623143);This is a study of the British state's generation, suppression and manipulation of news to further foreign policy goals during the early Cold War. Bribing editors, blackballing "unreliable" journalists, creating instant media experts through provision of carefully edited "inside information", and exploiting the global media system to plant propaganda - disguised as news - around the world: these were all methods used by the British to try to convince the international public of Soviet deceit and criminality and thus gain support for anti-Soviet policies at home and abroad.Britain's shaky international position heightened the importance of propaganda. The Soviets and Americans were investing heavily in propaganda to win the "hearts and minds" of the world and substitute for increasingly unthinkable nuclear war.